Back Cover: Bioinspired Synthesis of Cu2+‐Modified Covalent Triazine Framework: A New Highly Efficient and Promising Peroxidase Mimic (Chem. Eur. J. 46/2017). Issue 46 (7th July 2017) - Xiong, Yuhao; Qin, Yuemei; Su, Linjing; Ye, Fanggui
Abstract : Artificial enzyme mimics have attracted considerable attention due to their unique advantages over natural enzymes. Herein, an efficient peroxidase mimic based on a copper‐modified covalent triazine framework (CCTF) is reported, which possesses a unique specific surface area, atomically dispersed active Cu sites, efficient electron transfer properties, and an enhanced photo‐assisted peroxidase‐like activity. More importantly, the peroxidase‐like activity of the CCTF could be cooperatively modulated. The work provides new insights for the design and synthesis of peroxidase mimics based on CCTFs. More information can be found in the Full Paper by F. Ye et al. onpage 11037 .